Horizonte humanista e fenomenologia na geografia: o problema da assimilação humanista do pensamento de Martin Heidegger - Santos, Josimar Monteiro (2017)
The proposed research is established by the relation between two basic elements, on one hand the humanist horizon in Geography, and on the other hand the phenomenology. The articulation of these elements in the proposed research is made through the problematization of the humanist reading dispensed to the thinking of Heidegger in the humanist horizon of the geographic science. The general objective of the research is to confirm that the thinking of Heidegger is frontally incompatible with any modality of Humanism, in spite of the fact that the very constitution of Humanist Geography in the 1970s has developed through affiliation with phenomenology, highlighting in this context the express reference to the work of Heidegger. This objective is justified when the current state of the art on the subject in the discipline is observed, although this incompatibility has already been brought to the surface in the internal debate of geographical science in a clear way since the mid-1980s. The request for the thinking of Heidegger as a phenomenological matrix for the humanist perspective remained reproducing in subsequent decades as recent publications attest to the affiliation of the philosopher to the humanist perspective in geography. This is a recurrent reading in the directions that has developed in the Brazilian research linked to humanistic Geography especially since the 1990s. In this way, it is intended to contribute to the geographic research on the subject, evidencing that the humanist reading of the philosopher tends to obstruct the primary purpose that should lead to the relation between a particular science, in this case Geography, and Heidegger's thought, the know how to: “rehabilitate” research on the ontological basis of the respective science. This would imply the need for the geographer to assume the analytic of being-there (exposed paradigmatically in “Being and Time”) as the guiding thread to ontological investigation through phenomenology-hermeneutics of Heidegger; for the philosopher, the source of the fundamental ontology from which all ontologies would derive.